EFEKTIVITAS PENEGAKAN HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA PENGRUSAKAN FASILITAS UMUM DALAM AKSI UNJUK RASA (STUDI KASUS DI KOTA MAKASSAR): EFFECTIVENESS OF CRIMINAL LAW ENFORCEMENT AGAINST PERPETRATORS OF CRIMINAL DESTRUCTION OF PUBLIC FACILITIES IN RALLIES (CASE STUDY IN MAKASSAR CITY) - Luthfiyah S, Rifqah; Hamid, Abd. Haris; Rusli, Muhammad (Clavia, 2021)
This study aims to find out the extent of the effectiveness of law enforcement against perpetrators of destruction of public facilities in rallies and to find out the factors that influence the destruction of public facilities in rallies. This research is a type of normatife-empirical research, this type of research is a combination of normative approach with the addition of various empirical elements. This research was conducted in the city of Makassar, especially in the Makassar Resort Police (Polrestabes), makassar State Prosecutor's Office,41and Bosowa University. All data obtained from interviews, data documentation mauun poll data and analysts used, namely qualitative deskriftif analysis. The results of this study show that the extent of effectiveness of law enforcement against perpetrators of destruction of public facilities in rallies is the author considers that the effectiveness of law enforcement against perpetrators of destruction of public facilities carried out by the authorities has been effective, because cases of destruction of public facilities in rallies decreased from 2018 to 2019. In particular, the security forces who have handled every rally that led to riots that led to the destruction of public facilities. One thing to know, that efforts to handle law enforcement by the police must be far from arbitrary actions against perpetrators of destruction of public facilities, and still pay attention to the rights owned by the perpetrators. As for the factors that influence the destruction of public facilities in rallies are rallies because by damaging public facilities, the new government wants to meet the participants of the rallies, feel that their voice as a people is not well received and the absence of a response from the government so that some parties vent their anger to damage public facilities, the provocation of irresponsible parties , dissatisfaction with the government's decision, and the heartache of the participants of the rallies when their aspirations were not listened to.